2016
DOI: 10.4067/s0717-75262016000100010
|View full text |Cite
|
Sign up to set email alerts
|

Investigación en intervención breve y consumo de alcohol durante la gestación: productividad e impacto

Abstract: RESUMENObjetivo: Describir la producción científica de las Intervenciones Breves (IB) para disminuir el consumo de alcohol durante la gestación y cuantificarla mediante indicadores bibliométricos. Método: Se realizó un estudio de investigación secundaria con un diseño de revisión estructurada que consistió en búsquedas sistemáticas en las bases de datos Lilacs, PsycINFO, PubMed, Scielo y Scopus. Para el análisis se accedió al documento completo y se registraron características y procedimientos de aplicación de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…Nevertheless, in our context there is still a gap on reports of HED and its prediction by TPB in college students. Research in relation to the TPB and HED is mostly developed in Englishspeaking countries, and studies in Latin America are scarce (Lichtenberger, Conde, & Peltzer, 2013). Therefore, this study will also provide information for the design of preventive measures for this consumption pattern; a significant contribution in relation to the predictive power of the theory in different contexts than where it has been studied.…”
mentioning
confidence: 99%
“…Nevertheless, in our context there is still a gap on reports of HED and its prediction by TPB in college students. Research in relation to the TPB and HED is mostly developed in Englishspeaking countries, and studies in Latin America are scarce (Lichtenberger, Conde, & Peltzer, 2013). Therefore, this study will also provide information for the design of preventive measures for this consumption pattern; a significant contribution in relation to the predictive power of the theory in different contexts than where it has been studied.…”
mentioning
confidence: 99%
“…Furthermore, the results presented here could be useful to the discussion about the cross-cultural validity of the analyzed screening tools to assess AUDs in prenatal care settings, particularly regarding the less broadly used instruments, like the T-ACE, the TWEAK or the RAPS-QF. Even though the T-ACE and the TWEAK have been used and recommended for screening pregnant women in other cultural contexts, 46 our results show that the AUDIT has the best performance in screening for AUDs among Argentinean pregnant women.…”
Section: Properties Of the Itemsmentioning
confidence: 63%
“…In prior studies, mostly from the US and Europe, the T-ACE and secondly the TWEAK were the most used and recommended screening tools in the target population, 46 probably because they were designed specifically for pregnant women. In that context, they both showed good sensitivity and specificity for detecting risk consumption and AUDs.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that both the T-ACE and TWEAK may perform better at cut-off points of 3 (Sarkar et al, 2010 ) or when the threshold for risk drinking is redefined (Chang et al, 2001), and this improves clinical utility of these instruments in identifying PAE (Montag, 2016 ; Chang et al, 2001). Nonetheless, both the T-ACE and the TWEAK screening instruments are considered to be the most effective screening tools for risk drinking in pregnant women in most countries (Lichtenberger et al, 2016 ; Seo et al, 2016 ).…”
Section: Screening Strategiesmentioning
confidence: 99%